Endoscopic management of tumors of minor ampulla: a multicenter study - Khalyfa, Ahamed A.; Ahsan, Nayab; Inam, Mahnoor; Ayub, Kamran (Endoscopy International Open, 2022)
Background and study aims Papillary and duodenal carcinoma are aggressive cancers with poor 5-year survival rates. Papillectomy is a well-established treatment for early-stage carcinoma of the major papilla. Tumors arising in the minor papilla are relatively rare and there is little research available on the endoscopic management of these tumors.Patients and methods The purpose of this study was to establish the safety and efficacy of endoscopic papillectomy in the management of minor papillary tumors. A total of six patients undergoing ERCP for papillectomy for minor papillary tumor at four hospitals were included in this study over a period of 5 years.Results Papillectomy was technically successful in all six patients. Pathology revealed adenoma in three patients, adenoma with high-grade dysplasia in one patient, carcinoma in one patient, and carcinoid tumor in one patient. For follow-up, one patient had an additional tumor identified at 2 years which was found to be a recurrence of the original adenoma. This patient was treated with repeat papillectomy with no further evidence of recurrence.Conclusions In our pilot study, we demonstrate that endoscopic papillectomy appears safe and effective in the management of minor papillary tumors.